2022
DOI: 10.3389/fphys.2022.801829
|View full text |Cite
|
Sign up to set email alerts
|

The “Second Hit” of Repair in a Rabbit Model of Chronic Rotator Cuff Tear

Abstract: The rabbit supraspinatus is a useful translational model for rotator cuff (RC) repair because it recapitulates muscle atrophy and fat accumulation observed in humans after a chronic tear (the “first hit”). However, a timeline of RC tissue response after repair, especially with regard to recent evidence of muscle degeneration and lack of regeneration, is currently unavailable. Thus, the purpose of this study was to characterize the progression of muscle and fat changes over time after the repair of a chronic RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 39 publications
(71 reference statements)
0
13
3
Order By: Relevance
“…Previous studies have used rabbits to explore the impact of tenotomy on morphometric changes in the rotator cuff muscles. 21 , 33 , 34 , 35 Ward et al 21 , 33 reported that MyHC I fibres accounted for approximately only 10–20% of the composition of normal supraspinatus muscles, and this differs from the results of our study. In these two studies, the authors analysed the Myosin heavy chain (MHC) content using sodium dodecylsulfate–polyacrylamide gel electrophoresis.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Previous studies have used rabbits to explore the impact of tenotomy on morphometric changes in the rotator cuff muscles. 21 , 33 , 34 , 35 Ward et al 21 , 33 reported that MyHC I fibres accounted for approximately only 10–20% of the composition of normal supraspinatus muscles, and this differs from the results of our study. In these two studies, the authors analysed the Myosin heavy chain (MHC) content using sodium dodecylsulfate–polyacrylamide gel electrophoresis.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have used rabbits to explore the impact of tenotomy on morphometric changes in the rotator cuff muscles 21,33–35 . Ward et al 21,33 reported that MyHC I fibres accounted for approximately only 10–20% of the composition of normal supraspinatus muscles, and this differs from the results of our study.…”
Section: Discussioncontrasting
confidence: 97%
“…Lastly, the different expression pattern of the regenerative markers MYH8 and MYL4 [ 34 ] in healthy vs. torn supraspinatus muscle and even within torn muscle is highly interesting because the degeneration of rotator cuff is still considered irreversible in human [ 15 , 38 ] and animal models [ 28 , 39 ], and it is unclear why certain fibers appear to regenerate while others do not. However, the current dataset was intended to evaluate the use of the technology and its nature only allows qualitative analysis.…”
Section: Discussionmentioning
confidence: 99%
“…To replicate a rotator cuff tear, tenotomy of the supraspinatus was performed in the rabbit model, and tissues were harvested as previously described [ 3 , 28 , 29 ]. All animals were female New Zealand White and skeletally mature (6 months old, 4.35 ± 0.2 kg).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation